Immunoexpression of HER family, neuregulin, MAPK and AKT in invasive ductal carcinomas of the breast - (:unkn) unknown (IMR PRESS, 2008)
Background: The purpose of this study was to investigate the frequency of expression of the erbB/HER family of growth factor receptors, their ligand neuregulin alpha (NRG alpha) and the most important pathways activated by HER receptors that are mitogen-activated protein kinase (MAPK) and serine/threonine kinase (AKT) in invasive ductal carcinomas of the breast, not otherwise specified (IDC-NOS). Methods: 59 of the IDC-NOS of the breast were studied for ER, PR, EGFR, c-erbB-2, c-erbB-3, c-erbB-4, neuregulin Ab-3, phospho-AKT, and phospho-p44/42 map kinase using the streptavidin-biotin horseradish method. Results: Of the 59 tumours, 44 (75%) were ER+, 37 (63%) PR+, four (7%) EGFR+, seven (12%) c-erbB-2+, seven (12%) c-erbB-3+ and 14 (24%) c-erbB-4+alpha Strong cytoplasmic and/or nuclear immunoexpression was revealed in 17 (29%) cases for NRG alpha, 13 (22%) cases for p-AKT, and nuclear immunoexpression with p-MAPK was found in 17 (29%) cases. Conclusion: The results suggest that high-grade breast carcinomas are not only associated with ER/PR- negativity, but seem to be activated by receptor tyrosine kinase growth factors.
Keywords: breast carcinoma; HER family; immunohistochemistry; FACTOR RECEPTOR EXPRESSION; CANCER; OVEREXPRESSION; COEXPRESSION; PROGNOSIS; HER-2/NEU; C-ERBB-2; PREDICTS; SURVIVAL; MEMBERS